An assessment of strategies to control dental caries in Aboriginal children living in rural and remote communities in New South Wales, Australia - Yvonne Dimitropoulos; Alexander Holden; Kylie Gwynne; Michelle Irving; Norma Binge; Anthony Blinkhorn (BMC, 2018)
Abstract Background A community-led oral health service for Aboriginal people in Central Northern NSW identified the need for oral health promotion, as well as dental treatment; in three remote communities with limited access to dental services. A three-stage plan based on the Precede-Proceed model was used to develop a school-based preventive oral health program. The program will be piloted in three schools over 12 months aimed at improving the oral health of local Aboriginal children. Methods The proposed program includes four components: daily in-school toothbrushing; distribution of free fluoride toothpaste and toothbrushes; in-school and community dental health education and the installation of refrigerated and chilled water fountains to supply a school water bottle program. Primary school children will be issued toothbrushing kits to be kept at school to facilitate daily brushing using a fluoride toothpaste under the supervision of trained teachers and/or Oral Health Aides. School children, parents and guardians will be issued free fluoride toothpaste and toothbrushes for home use at three-monthly intervals. Four dental health education sessions will be delivered to children at each school and parents/guardians at local community health centres over the 12 month pilot. Dental education will be delivered by an Oral Health Therapist and local Aboriginal Dental Assistant. The program will also facilitate the installation of refrigerated and filtered water fountain to ensure cold and filtered water is available at schools. A structured school water bottle program will encourage the consumption of water. A process evaluation will be undertaken to assess the efficiency, feasibility and effectiveness of the pilot program. Discussion The proposed program includes four core evidence-based components which can be implemented in rural and remote schools with a high Aboriginal population. Based on the Precede-Proceed model, this program seeks to empower the local Aboriginal community to achieve improved oral health outcomes. Trial registration TRN: ISRCTN16110292 Date of Registration: 20 June 2018.